Experimental and numerical investigation of heave damper hydraulic seal for racing car - Azar, Michel; Grasso, Marzio; Rose, Timothy; Carless, Owen; St Leger-Harris, Chris; Lawson, Carl (Elsevier, 2022)
This article presents a combined experimental and numerical approach to analyse the failure of a heave damper hydraulic seal for racing car. The post-mortem analysis of the damaged seals was carried out with both optical microscopy and finite element analysis using material test data from Dynamic Modulus Analyser (DMA). The stress in the seal and damper was simulated modelling each step including the press-fitting on the piston, the interference with the cylinder and the oil pressure due to the service. The combination of the evidence collected from the numerical simulation and the observation of the surface damages on the seals proved that the cause of failure was the insufficient lubrication during high frequency, short stroke applications since these working conditions induce oil film break. The detailed damage mechanisms have been identified and explained and an alternative seal design that requires further study and testing in this application has been proposed.
Keywords: Heave damper; Rubber seal; PTFE; Press-fit; High-pressure fluid